Accumulated bladder wall dose is correlated with patient-reported acute urinary toxicity in prostate cancer patients treated with stereotactic, daily adaptive MR-guided radiotherapy. (June 2022) - Willigenburg, Thomas; van der Velden, Joanne M.; Zachiu, Cornel; Teunissen, Frederik R.; Lagendijk, Jan J.W.; Raaymakers, Bas W.; de Boer, Johannes C.J.; van der Voort van Zyp, Jochem R.N.
Highlights: Dose accumulation provides estimation of the dose delivered with MR-guided SBRT. Accumulated bladder (wall) dose was calculated for 130 prostate cancer patients. Bladder (wall) dose was correlated with patient-reported acute urinary toxicity. Mean dose to the bladder (wall) showed the highest correlation. Based on AUC, bladder wall parameters showed stronger correlations with the outcome. Abstract: Background and purpose: Magnetic resonance (MR)-guided linear accelerators (MR-Linac) enable accurate estimation of delivered doses through dose accumulation using daily MR images and treatment plans. We aimed to assess the association between the accumulated bladder (wall) dose and patient-reported acute urinary toxicity in prostate cancer (PCa) patients treated with stereotactic body radiation therapy (SBRT). Materials and methods: One-hundred-and-thirty PCa patients treated on a 1.5 T MR-Linac were included. Patients filled out International Prostate Symptom Scores (IPSS) questionnaires at baseline, 1 month, and 3 months post-treatment. Deformable image registration-based dose accumulation was performed to reconstruct the delivered dose. Dose parameters for both bladder and bladder wall were correlated with a clinically relevant increase in IPSS (≥ 10 points) and/or start of alpha-blockers within 3 months using logistic regression. Results: Thirty-nine patients (30%) experienced a clinically relevant IPSS increase and/or started with alpha-blockers. Bladder D5cm 3, V10–35Gy (in %), and Dmean and Bladder wall V10–35Gy (cm 3 and %) and Dmean were correlated with the outcome (odds ratios 1.04–1.33, p -values 0.001–0.044). Corrected for baseline characteristics, bladder V10–35Gy (in %) and Dmean and bladder wall V10–35Gy (cm 3 and %) and Dmean were still correlated with the outcome (odds ratios 1.04–1.30, p -values 0.001–0.028). Bladder wall parameters generally showed larger AUC values. Conclusion: This is the first study to assess the correlation between accumulated bladder wall dose and patient-reported urinary toxicity in PCa patients treated with MR-guided SBRT. The dose to the bladder wall is a promising parameter for prediction of patient-reported urinary toxicity and therefore warrants prospective validation and consideration in treatment planning.